Trabajadores de lo escrito, materias de la información - Jérôme Denis; David Pontille (Revue d'anthropologie des connaissances)
As the transparent circulation of information became a watchword for data flows, this text underlines the crucial role of the work done behind the scenes of telecommunication networks, whether in science, law, administration, cultural industries or service innovations. Pointing to the contribution of infrastructure studies to an anthropology of knowledge, it invites us to broaden the range of situations usually investigated, by highlighting three main aspects: the multiple forms of the work invisibility, the commitments and judgments at the core of the writing production, and the heterogeneity of the materials that make up the information produced on a daily basis within scriptural infrastructures.